Relationship between cluster miR-143/145 micro-RNAs with oncogenesis: tissue and cellular context - E. N. Voropaeva; T. I. Pospelova; A. M. Nesterets; V. N. Maksimov (Сибирский онкологический журнал, 2023)
The purpose of the study was to present up-to-date data on the regulation of expression, function in normal tissues and multidirectional activity in the oncogenesis of miR-143/145 microRNAs cluster, as well as to evaluate the possibilities and limitations of the therapeutic use of microRNAs of this cluster in malignant neoplasms. Material and methods. The search for available domestic and foreign literary sources published in PubMed and RSCI databases over the past 10 years has been carried out. 427 articles were found, of which 41 were included in this review. Results. The conservative cluster miR-143/145 is one of the most intensively studied in tumors. Based on the results of the analysis of differential miRNA expression, in vitro experiments in cancer cell lines and in vivo in mouse tumor models, a decrease in miR-143 and miR-145 levels was shown in malignant neoplasms of epithelial origin. Until recently, these miRNAs were considered classical oncosuppressors. The data presented in the review demonstrate that the results of a number of studies taking into account the cellular aspects of microRNA expression contradict this concept. miR-143 microRNA, for example, is known to participate in the metabolic restructuring of the tumor and the activation of neoangiogenesis. It has been shown that the oncosuppressive or pro-oncogenic activity of miR-143 and miR-145 depend on the tissue and cellular context and can be explained by the presence of several regulated targets that have opposite effects on oncogenesis. Taken together, the data obtained suggest the need to exercise caution when choosing the microRNAs of the described cluster for exogenous therapeutic delivery. Conclusion. Further detailed decoding of the mechanisms of miR-143 and miR-145 functioning in various types of tissues and cells, as well as identification of new MRNA targets are necessary for a better understanding of the involvement of these molecules in oncogenesis.